Psychological Impact of Parental Physical Violence on Children (Case Study of Child Abuse Victims) - Nadia, Salwa (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Violence is a deliberate behavior by an individual towards another individual and can cause physical and psychological harm, violence is an act of intimidation carried out by a stronger party against a weaker party. Violence can take various froms, namely physical, mental and sexual violence. The method used by the researcher is qualitative research with a case study approach model. Case study is a model that focuse on the exploration of a “ bounded system” on one praticular case or on some cases in detail by exploring data in depth. The results of the interview showed that the researcher saw that several children were just keeping quiet without any respons to the violence that had happened to their children. Keywords: Physical Violence, Parents, Children Victims Of Violence.